PENDIDIKAN KESEHATAN PADA IBU BEKERJA TENTANG ASI EKSKLUSIF DAN PENDAMPINGAN PEMBERIAN ASI DI RW V KELURAHAN KALIPANCUR KECAMATAN NGALIYAN - Arum Meiranny (Universitas Muhammadiyah Semarang, 2017)
Exclusive breast milk is the first, main and best food for the baby, which is natural. Breast milk contains various nutrients needed in the process of growth and development of infants (Prasetyono, 2009). Benefits of breast milk is so large as breast milk can reduce the risk of infants suffering from various diseases. If the sick baby will recover faster when breastfed. Breast milk also helps the growth and development of children's intelligence. According to the study, non-breastfed children had an IQ (Intellectual Quotient) lower 7 to 8 points compared with exclusively breast-fed children. Because in breast milk there are nutrients needed for infant brain growth that are absent or very little present in cow's milk, among others: Taurine, Lactose, DHA, AA, Omega-3, and Omega-6 (Nurheti, 2010). Although breastfeeding and breastfeeding are beneficial, but not yet fully implemented, an estimated 85% of mothers in the world do not breast feed optimally.Number of working mothers in RW V Kelipahan Kalipancur District Ngaliyan who have infants under 6 months as many as 9 people. The problem is that when the mother begins to work because the leave is over, they are confused to breastfeed their babies, so they finally choose to feed their baby formula. The solution ofthis problem aims to optimize the willingness and ability of working mothers to be able to provide exclusive breastfeeding. The resulting output is the application of science and technology and the increase in the quantity and quality of exclusive breastfeeding.Implementation of activities with the implementation / transfer of science and technology conducted directly on April 6, 2017 with the target of working mothers in RW V Kelipahan Kalipancur District Ngaliyan.IPTEK transfer form begins with a pre test and ends with a post test, education is delivered with an easy to understand method that gives material about the importance of breast milk and breastfeeding, the difference between breast milk and formula milk, how to milk milk, how to save milk, how to give breast milk, withdemonstrations. All participants tried to milk milk directly at the time with the equipment provided by the applicant to each mother.The level of cadre understanding of pre test and post test increased by 4.45%, the participants were able to milk ASI as taught and could use the existing equipment. The most important part of this activity is that mothers will transfer or teach other breastfeeding mothers, either in this area or in the office.Key Words: Breast milk, mother working and breastfeeding, breastfeeding